EKSPRESI SEBAGAI WAHANA PEMBENTUK FOTOGRAFI POTRET YANG FOTOGENIK - Mujisoewasta Mujisoewasta (Gelar : Jurnal Seni Budaya, 2009)
Selection of a subject in a photographic activity, that a human being is a most interesting subject to pay attention. Actually, it is not seen from her or his physical appearances such as his handsome face or her pretty face, her elegance and so forth. These are physical in nature and they have small attractive features, whereas the truly strongest attraction will appear from his or her poses or styles and expressions. A human being is a dynamic, ever-changing, ever-styled subject in expressing his or her feelings through his other faces and it is often attractive. It is frequently inciting a photographer to document it into an attractive photographic work (photogenic). An expression that is selected carefully and properly and by waiting and observing the subject patiently and thoroughly, and then a quick and accurate reaction is needed to determine timing of picture taking, because the expressions that area facial expression (mimic), movement or style may last for a few seconds. The most interesting expression is a dynamic one. However, it is very difficult to obtain because an acute and smart observation of a photographer is needed in graphically documenting the subject. A photographic work would be considered successful if it was able to document an interesting mimic or expression (photogenic). Without expression, a photographic work or portrait will appear to be rigid, insipid and unimpressive for people who look at it.Keyword : Expression, photographic capability, subject pose